2021
DOI: 10.3390/ijerph18168262
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Integral Morphotype of Competitive Amateur Athletes and Its Potential Relation with Recurrent Low Back Pain

Abstract: Athletes have higher thoracic and lumbar curvature in standing than the reference values of the non-athletic population. The sagittal integral morphotype method (SIM) assessment has not previously been applied to competitive amateur athletes (CAA). The propose of the present study was to determine the SIM of CAA treated at a sports-medicine center and to identify spinal misalignments associated with recurrent low back pain (LBP). An observational analysis was developed to describe the SIM in 94 CAA. The thorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Lumbar curvatures in the slump sitting and trunk forward bending positions, together with height, have been recently found as predicting factors of sciatica history in female classical ballet dancers [ 32 ]. Recurrent lower back pain has been related to the lumbar curve during trunk flexion, as well as reduced hamstring extensibility [ 33 , 59 ]. Hamstring length and demands are factors to consider in future analyses of rowers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lumbar curvatures in the slump sitting and trunk forward bending positions, together with height, have been recently found as predicting factors of sciatica history in female classical ballet dancers [ 32 ]. Recurrent lower back pain has been related to the lumbar curve during trunk flexion, as well as reduced hamstring extensibility [ 33 , 59 ]. Hamstring length and demands are factors to consider in future analyses of rowers.…”
Section: Discussionmentioning
confidence: 99%
“…At present, thoracic and lumbar kyphosis during rowing technique have not been related to the impact of a standardised clinical spine assessment. The specific impact of this sport on spine alignment requires an assessment that allow comparisons with other disciplines [ 1 , 3 , 4 , 10 , 12 , 13 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low back pain (LBP) is 1 of the most common injuries experienced by athletes, and female athletes are more likely to develop LBP than male athletes, [1] possibly because of their anatomical characteristics, smaller muscle mass, and lower bone densities. [2] In addition to the high prevalence of LBP. It has been reported that the 1-year reoccurrence rate of LBP is between 24% and 54% in patients with a history of LBP.…”
Section: Introductionmentioning
confidence: 99%